APRESIASI TARI DAERAH SEBAGAI MEDIA PENDIDIKAN KARAKTER MAHASISWA PGMI UNIVERSITAS MUHAMMADIYAH MATARAM - Hasanah, Niswatun; Samrin, Samrin; Verliyanti, Verliyanti (Ibtida'iy : Jurnal Prodi PGMI, 2024)
Arts education is using art as a medium for character education for humans. However, there are still many who think that art is only for fun with no clear benefits. The use of art in higher education has not gone well considering the assumption that art, especially dance, is only related to movement skills. Unfortunately, it is assumed that women are better at dancing than men and that women are more "flexible" in dancing. Men who can dance are considered strange and dance is considered unable to improve cognitive or affective abilities. Actually, dance can be used as an educational character for students. The values contained in a dance can be used as an educational medium. Movement skills in arts education are not the main focus. Students do not need to be flexible in dancing, but the most important thing is the values in dance that can be conveyed to shape the student's character. In this article, the inaq tegining amaq teganang dance is used to appreciate traditional dance and as a medium for character education for students.